NEW INSIGHTS INTO COMMUNNICATIONS AND ARTS RESEARCH - Will, Ralf G (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2024)
Are you a hater of Jews, an anti-Semite, once you call for a ceasefire in current Gaza war? New insights into media and communications as well as Arts and creativity research will debunk implications of this highly controversial query. Yet a valid and outrageous insinuation proposed by members of the political and cultural elite in Germany. Namely when dealing with the protest staged by a number of directors and actors who had particpated in the grand Finale of the famous film festival, Berlinale, in February of this year. Said creators and participants in the movie industry had held up signs and placards, calling for an immediate ceasefire in the Gaza war between the near-fascist Netanjahu regime and Hamas.